The Role of Room Attendant Supervisor in Improving The Quality of Room Attendant Work at Sthala A Tribute Portfolio Hotel Ubud Bali - Widiani, Desak Made; Wisnawa, I Made Bayu; Wirya, I Made Suwitra (Jurnal Manajemen Pelayanan Hotel, 2023)
The successful development of the tourism industry must be supported by facilities to satisfy and provide tourism services, including hotels, to tourists. However, during COVID-19, there was a reduction in the workforce and the number of linens, which resulted in less quality in the workforce and made guests complain because they felt less clean and comfortable. Supervisors play a significant role in improving the quality of room attendant work, the quality of service, and the smooth operation of hotel work. This study aims to determine the role of the room attendant supervisor in improving the quality of the room attendant's work, to find out the constraints of a room attendant supervisor in improving the quality of the room attendant's work, and to find out the efforts of the room attendant supervisor in overcoming these obstacles in improving the quality of the room attendant's work at Sthala, a Tribute Portfolio Hotel in Ubud, Bali. The method used is descriptive- qualitative. Data were collected from primary and secondary sources using observation, interviews, and documentation. The data were analyzed utilizing presenting results analysis to clarify what was obtained at the hotel. The results of this study indicate that supervisors must replace tools that need to be fixed. To improve the work discipline of their subordinates, supervisors must provide direction to their subordinates so that they can always report if there is a shortage of linen at work. Keywords: Improving Work Quality, Role of Supervisor, Room Attendant.